Infrastructure Delivery Systems Governance and Implementation Issues - Awuzie, Bankole Osita; McDermott, Peter (Management in the Built Environment,, 2019)
This book provides a framework for governing policy implementation by various stakeholders during the delivery of infrastructure projects. This framework relies on the tenets of the Viable Systems Model (VSM), a systems cybernetic model that enjoys a high level of acceptance in organizational analysis. The book presents a step-by-step guide for the multi-level governance of implementation during project delivery. Although the book focuses on the context of local content development policy and construction projects (infrastructure), it is presented in a manner that allows it to be adapted to other policies and sectors. The book includes a step-by-step methodology for assessing policy implementation in project or policy delivery systems. In addition, it shares insights into the probable challenges faced by the actors within the delivery system in achieving optimal implementation performance. Critical success factors are also highlighted, and illustrative diagrams of the framework are provided to facilitate understanding. The book is logically structured and presented in a straightforward manner. Also, the transposition of the VSM from a conventional organizational context to a multi-organizational context will appeal to readers with a background in systems thinking, monitoring or evaluation.